A study to assess the knowledge and practices of menstruation among rural adolescent girls - Hiremath, Bhavana R.; Shettar, Deepti (International Journal Of Community Medicine And Public Health, 2021)
Background: Adolescence is phase of maturations where an individual experiences drastic changes in growth and development. Age group 10-19 years is defined as adolescent age by World health organization. In developing countries, this is the period when many children drop-out of school and miss out on education. Among adolescent girls’ menstruation is a major life changing event. We conducted this study among rural adolescent girls to know their knowledge, attitude and practices towards menstruation. We also educated all girls on physiology and hygienic practices during menstruation. Methods: A cross-sectional study was conducted among adolescent girls attending our out-patient clinic in the rural area. All girls were interviewed to assess their knowledge and practices towards menstruation. Informed consent was taken from all girls before stating the study. Data presented in form of frequency, percentages. Chi-square test was applied to analyze for association. Results: 87% were students, 88% adolescent girls belonged to Below Poverty Line (BPL) families. 98% adolescent girls had attained menarche before 15 years of age, 27% adolescent girls had dysmenorrhea presenting as pain in abdomen region. Sanitary pad was being used by only 64% adolescent girls, of whom, 59.4% change sanitary pad twice daily, 75% dispose it by burning. Overall, 36% adolescent girls used cloth, of whom, 41.7% changed cloth twice a day, 69.4% adolescent girls wash and burn the cloth. Among adolescent girls still studying in school 71.2% used sanitary pads which was statistically significant. Conclusions: Education is essential to empower girls to take informed decisions. On receiving adequate information on menstruation, girls were willing to adapt healthy hygienic practices. Hence, health education activities should be started at all schools so as to inculcate good practices early in life.